Effect of water storage on the mechanical properties of zinc polycarboxylate cements - Yoruc, A. B. Hazar; Karaaslan, A. (INST MATERIALS PHYSICS, 2007)
This work was aimed to study the effect of water absorption on the mechanical properties of several zinc polycarboxylate cements by changing the samples' storage times. The water absorption of four commercial zinc polycarboxylate cements were measured using specimens immersed for 1 h to 840 h (35days) in distilled water. Hardness and compressive strength values were measured using specimens immersed for 1 day and 35 days in distilled water. All samples took up most of the water during the first 24 h. Poly-F Plus (PFP) and Durelon (D) cements absorbed less water than Adhesor Carbofine (AC) and Polycarboxylate WP (P) cements. Adhesor Carbofine (AC) is the most hydrophilic material among the polycarboxylate cements. Water altered the physical properties of polycarboxylate cements after 35 days of water storage. Water sorption also provoked an expansion in volume of the immersed specimens, ranging from 1.72% to 9.19%. PFP, AC and D cements were shown an important increase in the hardness for 1 day and 35 days in the water (PFP:32%, AC:22%, D:9%). However, P cement showed a decrease in the hardness (52%). The highest compressive strength was obtained with D (110 MPa), whereas the lowest value was observed with P (60 MPa). Water sorption (mu g/mm(3)), volume change (Delta V%), hardness (HV) and compressive strength (MPa) of zinc polycarboxylate cements were listed from high to low value: AC > P > PFP > D; AC > P > PFP > D; PFP > AC > P > D and D > PFP > AC > P.
Keywords: zinc polycarboxylate cements; water absorption, hardness; compressive strength; microstructure; GLASS-IONOMER CEMENTS; DENTAL RESTORATIVE MATERIALS; ORTHODONTIC CEMENTS; HARDNESS; RESIN; MICROHARDNESS; ABSORPTION; Science & Technology - Other Topics; Materials Science